(untitled) (Legal journal - Research in Legal and Social Sciences, 2024)
The article first shows how cybercrime has been progressively escalating in society. It also addresses the consequences generated by this form of committing punishable acts, starting from its main characteristics and particularities. Thus, the qualitative approach was used as a method, with a non-experimental design, documentary type, with a cross-sectional descriptive scope. The objective was to determine the basic types of punishable acts perpetrated through informatics, in order to outline a legislative analysis of the rules applicable to such cases, at national and international level. Also, it was deepened in what refers to the jurisprudence related to cybercrime cases, both in the Republic of Paraguay and abroad, thus verifying what kind of situations were presented. Finally, emphasis was placed on the seriousness of the anti-legal actions carried out through this modality, since this was the central point of the research work. It is concluded that cybercrime increases considerably with the scientific-computer evolution, since new ways of committing punishable acts are presented, which results in a notorious damage to society, so it is essential to deepen efforts to combat this modern evil.